Manajemen Kelas Inovatif untuk Pembelajaran Bahasa Arab: Membangun Lingkungan yang Mendorong Prestasi Bahasa - Ningsih, Wiwik Prasetiyo; Hamdy, Mohammad Zainal (Al-Abshar: Journal of Islamic Education Management, 2024)
Arabic, as the language of the Qur’an, holds a central position in Islamic education, particularly in traditional madrasahs. However, in Madrasah Miftahul Ulum Angsokah Timur, the learning outcomes for Arabic remain far from expectations. Various challenges hinder the success of Arabic language instruction, such as limited instructional hours (only two hours per week), students’ low proficiency, a shortage of qualified Arabic teachers (only two for all classes), and minimal parental support. Additionally, the learning objectives tend to focus merely on filling class schedules rather than fostering meaningful language competence. This study aims to explore and analyze how innovative classroom management strategies can create an engaging and effective learning environment that supports Arabic language achievement. Using a descriptive qualitative approach, data were collected through classroom observation, interviews with teachers and students, and document analysis. The findings reveal that the implementation of creative strategies—such as using song-based vocabulary instruction (Kamus Hijau), Arabic conversation and song competitions, video documentation uploaded to YouTube, and guided student-generated dialogues—significantly increased student motivation, confidence, and active participation. These strategies helped shift the classroom dynamic from teacher-centered to student-centered learning and encouraged greater language use in authentic contexts. The study contributes practical insights into Arabic language teaching in under-resourced madrasahs and demonstrates that limited resources can be overcome with pedagogical creativity and contextual adaptation. This research fills a gap in the literature by focusing on classroom management innovation in traditional Islamic schools with minimal facilities.